Characterization of the Rifamycin-Degrading Monooxygenase From Rifamycin Producers Implicating Its Involvement in Saliniketal Biosynthesis - Zheng, Xiao-Fu; Liu, Xin-Qiang; Peng, Shu-Ya; Zhou, Qiang; Xu, Bin; Yuan, Hua; Tang, Gong-Li (Frontiers in Microbiology, 2020)
Rifamycin derivatives, such as rifampicin, have potent antibiotic activity and have long been used in the clinic as the mainstay components for the treatment of tuberculosis, leprosy, and AIDS-associated mycobacterial infections. However, the extensive usage of these antibiotics has resulted in the rapid development of bacterial resistance. The resistance mechanisms mainly include mutations of the rifamycin target RNA polymerase of bacteria and enzymatic modifications of rifamycin antibiotics. One modification is the recently characterized rifamycin degradation catalyzed by Rox enzymes, which belong to the widely occurring flavin monooxygenases. Intriguingly, our recent sequence analysis revealed the rifamycin producers also encode Rox homologues that are not yet characterized. In this work, we expanded the study of the Rox-catalyzed rifamycin degradation. We first showed that the Rox proteins from rifamycin producers have the enzymatic rifamycin SV-degrading activity. Then we used structurally diverse rifamycin compounds rifampicin and 16-demethylrifamycin W to probe the substrate scope and found that they each have a slightly different substrate scope. Finally, we serendipitously demonstrated that Rox proteins can also catalyze the transformation of 16-demethylsalinisporamycin to 16-demethylsaliniketal A. Since 16-demethylsalinisporamycin and 16-demethylsaliniketal A are the counterpart analogues of salinisporamycin and saliniketal A, our biochemical findings not only uncover a previously uncharacterized self-resistance mechanism in the rifamycin producers, but also bridge the gap of the biosynthesis of the potential antitumor compound saliniketal A.